2018
DOI: 10.1002/ehf2.12313
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of percutaneous mitral valve edge‐to‐edge repair in patients with end‐stage heart failure awaiting heart transplantation

Abstract: AimsFunctional mitral regurgitation is complicating end‐stage heart failure and potential heart transplantation by increasing pulmonary artery pressures. The aim of the present study was to investigate feasibility and haemodynamic effects of percutaneous mitral valve edge‐to‐edge repair using the MitraClip™ device in patients with end‐stage heart failure awaiting heart transplantation.Methods and resultsIn this retrospective study, we identified nine patients suffering from end‐stage heart failure listed for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…We and others have demonstrated that PMVR is an option as 'bridge to transplant' in nonamyloid cardiomyopathy patients awaiting heart transplantation. 67 Although the majority of patients in the present study were too aged for a 'bridge to transplant' approach, our data may add to the idea that interventional treatment of MR may significantly extend the therapeutic possibilities for those critical ill patients.…”
Section: Heart Failure Due To Amyloid Cardiomyopathymentioning
confidence: 68%
“…We and others have demonstrated that PMVR is an option as 'bridge to transplant' in nonamyloid cardiomyopathy patients awaiting heart transplantation. 67 Although the majority of patients in the present study were too aged for a 'bridge to transplant' approach, our data may add to the idea that interventional treatment of MR may significantly extend the therapeutic possibilities for those critical ill patients.…”
Section: Heart Failure Due To Amyloid Cardiomyopathymentioning
confidence: 68%
“…9 Third, from a physiopathological perspective, PMVR reduces MR, thus decreasing left-side volume overload and pulmonary pressures and increasing cardiac output. 10 And fourth, this haemodynamic enhancement has translated into positive left ventricular remodelling and improvement in clinical symptoms, quality of life, and 6 min walk test in different series. [11][12][13] Although only modest increments in LVEF have been reported in this scenario, these changes, alongside the reduction in regurgitant volume, imply an improvement in antegrade ejection flow that might be one of the underlying mechanisms for a better cardiopulmonary performance.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, mean LVEDD was 71 mm before MC in our patients, pointing to a very sick cohort of patients with exceptionally poor outcomes and probably in many centres those patients would have been rejected for PMVR in contemporary practice. However, at our centre, we have conduced MC procedures in advanced HF patients over the last decade with respectable success, 7,16,33 documenting that PMVR is even feasible in patients with heavily dilated LV, when patients are carefully selected and the operator is experienced.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients with advanced HF, it remains unclear whether a prior MC implantation has any benefit as a bridge to LVAD. We have recently published that PMVR can be successfully used as a ‘bridge to transplant’ strategy in patients awaiting heart transplantation 33 . However, this is a situation where the aspired treatment strategy is not immediately available, making a ‘bridge to’ strategy necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation